Cataloguing cultural objects and digital dissemination of cultural heritage - Saorín, Tomás (Anuario ThinkEPI, 2011)
Having observed the progress of museums in the computerization of collections, the author warns about the need to ensure that the cataloguing efforts adopt appropriate technological solutions to produce value on Web 2.0. Metadata should be able to define complex cultural objects much more broadly than the simple description of a single piece or monument. Context and environment information should be added. Formal description processes should not be limited to inside the museum.
Keywords: Heritage; Museums; Cataloguing; Cultural objects; Computerization; Digitization; Metadata; Web 2.0